PENGARUH LAMA USAHA, UKURAN USAHA SERTA MODAL USAHA TERHADAP KINERJA UMKM DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI PADA UMKM DI SUMATERA UTARA - Herti Diana Hutapea; Vebri M Lumbangaol; Christnova Hasugian; Sahat Martupa Siahaan (JURNAL LENTERA BISNIS, 2024)
This study aims to determine the effect of length of business, business size and business capital on MSME performance with financial literacy as a moderating variable in MSMEs in North Sumatra. Data collection using questionnaire distribution via google form with whattsap. The sampling technique used convenience simple random sampling. Determination of the number of samples using the Hair J.F. formula, (2010) the number of representative samples is dependent on the number of indicators multiplied by 5 to 10. The number of samples in this study was the number of indicators x 5 = 17 x 5 = 85. So that the sample of this study was 85 MSME players assisted by the North Sumatra Province cooperative and UKM office. And in hypothesis testing using Smart PLS 4.0. The results showed that the length of business and business size had a positive and significant effect on the performance of MSMEs in North Sumatra and business capital had no effect on the performance of MSMEs in North Sumatra while financial literacy did not moderate the influence between length of business, business size and business capital on the performance of MSMEs in North Sumatra.